LEDs Could Borrow From Beetles. - Mullins, J.
This paper discusses the on how to improve LED's whiteness and effectivity in industrial applications. The concept is based on a shell of the Cyphochilus beetle. To achieve is, they have made a synthetic version of the beetle shell. One factor is that the beetle's whiteness may have the important industrial implications: the relatively large amount of empty space within the cuticle structure. It's at the interface between the cuticle filaments and the air in the spaces that light scattering takes place
Keywords: Cyphochilus beetle; LED; Cuticle filaments; Industrial applications; Light scattering; Synthetic beetle shell